Pengaruh Terapi Murrotal Terhadap Penurunan Tingkat Nyeri dan Kecemasan Saat Perawatan Luka Pasien Ulkus Dm Di Rsud K.R.M.T. Wongsonegoro Semarang - Dyah Restuning Prihati; Maulidta Karunianingtyas Wirawati (Program Studi S1 Keperawatan Universitas Ngudi Waluyo, 2018)
Diabetic ulcer is caused by damage to the skin nerves due to reduced blood flow. Pain and anxiety when wound care begins when dressing and cleaning the wound. Murottal therapy is a distraction technique in the form of al-quran records, decreases stress hormones and provides a feeling of relaxation. The purpose of this study was to reduce the level of pain and anxiety during wound care in patients with DM ulcers after being given murrotal therapy in RSUD K.M.T. Wongsonegoro Semarang. The research method with quasi experimental pre-posttest control group. a sample of 17 people in the intervention group and 15 in the control group. Sample selection with total sampling. The murrottal listening intervention group played for 3 times for 15 minutes. Respondents were conducted pre and posttest with NRS pain measuring instruments and DASS anxiety. The results of the Wilcoxon test in the intervention group obtained p = 0,000, there were differences in the level of pain between before and after murotal therapy and p = 0.002 there was a difference in the level of anxiety between before and after murotal therapy. In the control group obtained p = 0.02, there were differences in the level of pain between before and after murotal therapy and the value of p = 1.00, there was no difference in the level of anxiety between before and after given murotal therapy. Conclusion: Murrotal therapy can reduce the level of pain and anxiety during wound care for DM ulcer patients.